Discrimination of Holocene tephra units in Lake Van using mineral magnetic analysis. (30th August 2018) - Makaroğlu, Özlem; Çağatay, M. Namık; Nowaczyk, Norbert R.; Pesonen, Lauri J.; Orbay, Naci
Abstract: Detailed magnetic analysis of the four sediment cores from Lake Van, Eastern Turkey dating back to 9.4 cal ka BP were carried out for discriminating and correlating tephras and laminated sediments in four different cores. Six tephra units (T0, T1, T2, T3, T4 and T5) with distinct magnetic properties were identified in the cores. The tephra units are characterized by ferrimagnetic material, with a grain size in the pseudo single domain (PSD) range. There is no significant correlation between magnetic susceptibility peaks of the different tephra units except for the tephra T1 and T2. On the contrary ARM profiles show significant correlations as remanent magnetization indicators. The tephra units T1 and T2, have a higher magnetic susceptibility and a higher intensity of remanent magnetization, and finer grain size than the other tephra units. The results suggest that there is a clear difference between the magnetic properties of the different tephra units and the lake sediments. Our findings show that also differential deposition of volcanic material including magnetic mineral occurs during the transport with distance from the volcanic source.